547 Clinical Particularities in 2 Cases with Polyradiculoneuropathy. (October 2012) - Iurian, SI; Iurian, S; Gradinariu, G; Vidrighin, A; Mehedintu, B
Abstract : Background and Aims: Guillain-Barré syndrome (GBS) is an acute polyradiculoneuropathy with weakness and diminished reflexes. The authors present clinical peculiarities in 2 cases diagnosed with GBS. Methods: The authors present 2 cases: a 18 month-old male admitted because of unstable walking (1 st case) and severe lower extremities pain for the 2 nd case (5 year-old boy). Cases history: upper respiratory tract illness 3 weeks before symptoms onset; no vaccinations, surgical procedures or trauma prior to disease. Clinical exam: 1 st case presented respiratory signs (dysphonia, slurred speech, short breath); 2 nd case was admitted for severe legs pain. In addition, both cases were characterized by symmetrical extremities weakness, legs sensory changes (paresthesias, numbness), intense nuchal rigidity, positive Brudzinski sign, abolished osteo-tendinous reflexes in both upper/lower limbs and no abdominal reflexes. There were performed electromyography (EMG), nerve conduction velocity tests (NCT), serologic and cerebrospinal fluid (CSF) analysis. Results: CSF analysis identified albumino-cytologic dissociation: elevation of CSF protein with normal white blood cells count. The serologic studies shown normal titers for cytomegalovirus, Epstein-Barr virus and Mycoplasma. The NCT and EMG have proved severe demyelinating neuropathy and distal conduction block. Differential diagnosis: authors excluded meningitis, myopathies, poliomyelitis, polymyositis and myasthenic syndromes. The patients were treated with intravenous immunoglobulins with good clinical evolution. Conclusions: The authors presented 2 cases with GBS secondary to respiratory infections. Cases peculiarities. Even though small children have the lowest risk, 1 st case presented very early onset; Both cases presented intense nuchal rigidity.